Korean Red Ginseng Saponin Fraction Rich in Ginsenoside-Rb1, Rc and Rb2 Attenuates the Severity of Mouse Collagen-Induced Arthritis - Mehari Endale; Eun Ju Im; Joo Young Lee; Sung Dae Kim; Taddesse Yayeh; Yong-Bum Song; Yi-Seong Kwak; Chaekyun Kim; Seung-Hyung Kim; Seong-Soo Roh; Jae Youl Cho; Man Hee Rhee (Hindawi Limited, 2014)
Despite a multitude of reports on anti-inflammatory properties of ginseng extracts or individual ginsenosides, data on antiarthritic effect of ginseng saponin preparation with mixed ginsenosides is limited. On the other hand, a combined therapy of safe and inexpensive plant-derived natural products such as ginsenosides can be considered as an alternative to treat arthritis. Our previous in vitro data displayed a strong anti-inflammatory action of red ginseng saponin fraction-A (RGSF-A). We, herein, report a marked antiarthritic property of RGSF-A rich in ginsenoside Rb1, Rc, and Rb2. Collagen-induced arthritic (CIA) mice were treated with RGSF-A or methotrexate (MTX) for 5 weeks. Joint pathology, serum antibody production and leukocye activation, cytokine production in the circulation, lymph nodes, and joints were examined. RGSF-A markedly reduced severity of arthritis, cellular infiltration, and cartilage damage. It suppressed CD3+/CD69+, CD4+/CD25+, CD8+ T-cell, CD19+, B220/CD23+ B-cell, MHCII+/CD11c+, and Gr-1+/CD11b+ cell activations. It further suppressed anti-CII- or anti-RF-IgG/IgM, TNF-α, IL-1β, IL-17, and IL-6 secretions but stimulated IL-10 levels in the serum, joint, or splenocyte. RGSF-A attenuated arthritis severity, modified leukocyte activations, and restored cytokine imbalances, suggesting that it can be considered as an antiarthritic agent with the capacity to ameliorate the immune and inflammatory responses in CIA mice.